Intervening Role of Customer Satisfaction on QRIS Usage Intensity - Muhadjir Anwar; R. Ay. Adellia Meitylda Anwar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study explicitly investiigates the structural impact of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on the Usage Intensity of the QRIS feature within the “Blu” digital banking app, with Customer Satisfaction as a mediating variable. Methodology: Using quantitative descriptive approac. Data were collected from 100 purposively sampled Blu users in Indonesia. Analysis was performed via Partial Least Squares-Structural Equation Modeling (PLS-SEM) to rigorously test both direct and indirect path effects. Results: Analytical results confirm that PU and PEOU significantly drive usage intensity. Notably, mediation analysis reveals that Customer Satisfaction serves as a critical intervening mechanism, significantly amplifying the relationship between functional perceptions and sustained usage behavior. Findings: The study identifies satisfaction as the primary psychological bridge ensuring that technical usability translates into long-term user engagement and higher transaction frequency.. Novelty: This study contributes to the digital banking literature by emphasizing post-adoption behavior, particularly usage intensity, within the context of spesific digital banking platform. Originality: This research contributes to the Technology Acceptance Model by shifting focus from adoption to post-adoption within the Indonesian digital—only banking sector—a context currently underrpresented in fintech literature. Conclusion: Findings suggest digital banks must optimize both system functionality and user experience (UX) to foster the satisfaction necessary for continuous usage intensity. Type of Paper: This paper is an empirical research paper.